FORMATION OF QUALITY INDICATORS OF RAW SMOKED SAUSAGES INTO ACCOUNT THE INTENSIFICATION OF THE TECHNOLOGICAL PROCESS - Tatiana Barsukovskaya; Valentin Shipulin; Natalia Lupandina (Вестник Северо-Кавказского федерального университета)
Russian sausage products market is one of the fastest growing markets in the Russian food industry. Therefore, more and more Russian and Western companies see it as the most promising for development. It is known that the sausage products, including smoked sausages with long shelf life for a significant share of the national diet. Smoked meat products are some of the traditional types of sausages, characterized dense texture, pleasant flavor and taste specific, moreover, characterized by a small moisture content, a significant amount of fat and protein, whereby the highly energetic value. Smoked meat products containing lactic acid microflora positively affect the absorption of nutrients, their use has a beneficial effect on the prevention and the prevention of intoxication of the gastrointestinal tract of humans. However, the entire above product has merits in terms ofpractice and a significant drawback - the process ofproduction of this type ofproducts is one of the toughest in the sausage production, have a long and laborious. One of the objectives of the meat industry is to intensify the production of smoked sausages while improving the quality of manufactured products.